Effect of Adding Picung Seeds Paste and Storage Time on Total Lactic Acid Bacteria, Salmonella, Water Content and pH in Tilapia Fish: Pengaruh Penambahan Pasta Biji Picung dan Lama Penyimpanan Terhadap Bakteri Asam Laktat, Salmonella, Kadar Air dan pH pada Ikan Nila - Rochmah, Siti Fachria; Syafitri, Yosi; lianti, lita (Communication in Food Science and Technology, 2024)
Fish is one of the perishable food commodities caused by enzyme activity. The activity of microorganisms present in the body of fish or due to the process of oxidation of body fat through the air. The fermentation process is one way to extend shelf life. The fermentation process in fish can be done with the addition of preservatives such as picung. Picung seeds contain tannins and phenols which are antimicrobial compounds. The addition of picung seeds to fish can also help the growth of lactic acid bacteria if stored in a closed container because picung seeds contain carbohydrates, where sugar is converted into lactic acid. This study used quantitative descriptive methods and focused on the effect of variations in picung concentration (30%, 60% and 90%) as well as storage duration of 3 and 6 days at room temperature to determine the effect on total BAL, Salmonella, water content and pH. The results of this study showed that the addition of picung seeds and storage duration in tilapia can affect the total BAL, Salmonella, water content and pH, with the highest total BAL on the third day with a 60% picung seed paste concentration of 7,4 log CFU/g, negative Salmonella on day 6, then the moisture content value and pH value decreased until day 6